Information systems architecture and technology : proceedings of 40th anniversary International Conference on Information Systems Architecture and Technology - ISAT 2019.: proceedings of 40th anniversary International Conference on Information Systems Architecture and Technology - ISAT 2019. Part 2 ([2020]) - Unknown
No abstract available